2014
DOI: 10.1080/10426914.2014.880459
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Vanadium-Doped Zinc Oxide, Zn1–XVxO

Abstract: This work investigates the changes in the structural and magnetic properties due to the doping of vanadium in zinc oxide (with varying concentrations of vanadium, viz., 2%, 4%, and 6%) grown by solid state reaction method. The grown samples were analyzed through powder X-ray diffraction measurements, vibrating sample magnetometry (VSM), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDAX) analysis, and UV-vis spectroscopy. The electronic structure of grown Zn 1-x V x O has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…It was reported that the method of synthesis and preparation has an important effect on the morphology, homogeneity, photocatalytic performance, and sinterability of ceramic powders . Some approaches for synthesizing V‐doped ZnO particles and ZnO‐V 2 O 5 composites have been proposed including solid‐state reaction, sol‐gel, co‐precipitation method, decomposition method, etc. To the best of our knowledge, a study focused on the preparation of V‐doped ZnO via microemulsion method and its photocatalytic properties has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the method of synthesis and preparation has an important effect on the morphology, homogeneity, photocatalytic performance, and sinterability of ceramic powders . Some approaches for synthesizing V‐doped ZnO particles and ZnO‐V 2 O 5 composites have been proposed including solid‐state reaction, sol‐gel, co‐precipitation method, decomposition method, etc. To the best of our knowledge, a study focused on the preparation of V‐doped ZnO via microemulsion method and its photocatalytic properties has not been investigated.…”
Section: Introductionmentioning
confidence: 99%